Enhancement of DPP-IV inhibitory activity and the capacity for enabling GLP-1 secretion through RADA16-assisted molecular designed rapeseed peptide nanogels. Issue 9 (19th April 2022) - Xu, Feiran; Xu, Baocai; Chen, Hong; Ju, Xingrong; Gonzalez de Mejia, Elvira
Abstract : RADA16-assisted molecular designed rapeseed peptide nanogels were used to enhance the DPP-IV inhibitory activity and the capacity for enabling GLP-1 secretion in STC-1 cells. Abstract : The potential of pentapeptide IPQVS (RAP1) and octapeptide ELHQEEPL (RAP2) derived from rapeseed napin as natural dipeptidyl-peptidase IV (DPP-IV) inhibitors is promising. The objective was to develop a nanogel strategy to resist the hydrolysis of digestive and intestinal enzymes to enhance the DPP-IV inhibitory activity of RAP1 and RAP2, and stimulate glucagon-like peptide 1 (GLP-1) secretion of RAP2 by a RADA16-assisted molecular design. The linker of double Gly was used in the connection of RADA16 and the functional oligopeptide region (RAP1 and RAP2). Compared to the original oligopeptides, DPP-IV IC50 of the nanogels RADA16–RAP1 and RADA16–RAP2 decreased by 26.43% and 17.46% in Caco-2 cell monolayers, respectively. The results showed that the two nanogel peptides with no toxicity to cells had higher contents of stable β-sheet structures (increased by 5.6-fold and 5.2-fold, respectively) than the original oligopeptides, and a self-assembled fibrous morphology. Rheological results suggested that the nanogels RADA16–RAP1 and RADA16–RAP2 exhibit good rheological properties for potential injectable applications; the storage modulus ( G ′) was 10 times higher than the low modulus ( G ′′). Furthermore, the RAP2 and its RADA16-assisted nanogel peptide at the concentration of 250 μM significantly ( P < 0.05) increased the release of GLP-1 by 35.46% through the calcium-sensing receptor pathway in the enteroendocrine STC-1 cells. Hence, the innovative and harmless nanogels with the sequence of RADA16–GG–X n have the potential for use by oral and injection administration for treating or relieving type 2 diabetes.